2007
DOI: 10.1016/j.ymeth.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

A non-receptor-mediated mechanism for internalization of molecular chaperones

Abstract: The evolving realization that stress proteins, which have for many years been considered to be exclusively intracellular molecules under normal conditions, can be released from viable cells via a number of potential routes/pathways has prompted interest into their extracellular biology and intercellular signaling properties. That the stress proteins Hsp60, Hsp70 and gp96 can elicit both proand anti-inflammatory effects suggests that these molecules play a key role in the maintenance of immunological homeostasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
0
5
0
3
Order By: Relevance
“…Three gp96-receptors are known in humans: the α 2 -macroglobulin receptor CD91 [48], the scavenger receptors SR-A (Type A) [27] and SREC-I (Type F) [28], all involved in different signalling pathways. Also an unspecific uptake has been considered as possibly relevant in the uptake of gp96 [49]. In order to get an insight into the mechanism of self-induction future studies will aim at investigating release, uptake, and subsequent intracellular distribution of gp96.…”
Section: Discussionmentioning
confidence: 99%
“…Three gp96-receptors are known in humans: the α 2 -macroglobulin receptor CD91 [48], the scavenger receptors SR-A (Type A) [27] and SREC-I (Type F) [28], all involved in different signalling pathways. Also an unspecific uptake has been considered as possibly relevant in the uptake of gp96 [49]. In order to get an insight into the mechanism of self-induction future studies will aim at investigating release, uptake, and subsequent intracellular distribution of gp96.…”
Section: Discussionmentioning
confidence: 99%
“…Internalization of Hsp10 by target cells is likely to occur since it has been shown that other chaperones (e.g., gp96) can enter into the cell via non-specific endocytosis/pinocytosis (Pockley et al 2007). Although a specific receptor for Hsp10/EPF has not yet been described, one can speculate that this molecule could be internalized with participation of the type of receptors listed in the previous paragraph, or via non-receptor-mediated mechanisms as mentioned above for gp96.…”
Section: Epf and Its Target Receptorsmentioning
confidence: 99%
“…As proteínas do choque térmico são expressas em condições fisiológicas, constituindo cerca de 5 a 10% de proteínas totais (POCKLEY et al, 2007), mas sua expressão aumenta em situações de estresse como de meio ambiente (choque térmico, radiação ultravioleta, metais Imunologistas se dividem em diferentes linhas de pesquisa quanto ao estudo das propriedades das HSP: quanto aos seus efeitos extracelulares como sendo sinalizador de "perigo" ao sistema imune (CHEN et al, 1999;BREOLER et al, 2001;GALLUCCI;MATZINGER, 2001;WALLIN et al, 2002) e potente agente inflamatório; e quanto aos seus efeitos anti-inflamatórios (POCKEY et al, 2008).…”
Section: Heat Shock Proteins (Hsps)unclassified
“…Na inflamação, a HSP 60 via TLR2 (mas não o TLR4) pode induzir a ativação da integrina B1 em linfócitos T humanos e aumentar a adesão dessas células (ZANIN-ZHOROV et al, 2003). As proteínas do choque térmico servem também como um estímulo endógeno para o receptor de sinalização Toll/IL-1 (TIR) que utiliza TLR2 e TLR4 (VABULAS et al, 2002), mas para que isso ocorra, primeiramente a HSP 60 precisa ser internalizada a fim de estimular a via de sinalização do TIR nos macrófagos (VABULAS et al, 2001) ou pelas células dendríticas (DC) por meio de um mecanismo mediado não por receptor (POCKLEY et al, 2007 (CIOCCA et al, 1996;TABIBZADEH et al, 1996), na decídua durante a fase de gestação inicial (NEUER et al, 1999), e também no cordão umbilical (LI et al, 1996). Divers et al (1995) A implantação embrionária está associada à placentação, processos determinantes no estabelecimento da comunicação materno-fetal em cada espécie (LEISER; KAUFMANN, 1994;MARQUES et al, 2007).…”
Section: Heat Shock Proteins (Hsps)unclassified
See 1 more Smart Citation